Contribuição da Política de Assistência Social no enfrentamento à seca no Amazonas no período de 2023 a 2024 - Marques, Bruna Leonarda Belém (Brasil, 2025)
The Amazon has been experiencing one of the worst climate crises in recent years, from 2023 to 2024. For example, the state of Amazonas is suffering from the difficulties exposed by the sec. In view of this, it was necessary to raise the discussion on how the Social Assistance Policy is implemented in this context, highlighting the actions carried out by the state government and the State Secretariat of Social Assistance. As a methodological contribution, it is based on a bibliographic and documentary review on the subject. With this quantitative and qualitative research, it can be concluded that there is a need to rethink the implementation of Social Assistance, so that the people of this region are seen as beings with rights, and who need to have access to policies such as Assistance, and such policy needs to be managed by autonomous professionals, aiming to act with actions beyond immediacy.